Importance of Maternal Persistence in Young Children's Persistence - Imafuku, Masahiro; Saito, Atsuko; Hosokawa, Kenchi; Okanoya, Kazuo; Hosoda, Chihiro (Frontiers in Psychology, 2021)
Persistence of a distant goal is an important personality trait that determines academic and social success. Recent studies have shown that individual differences in persistence involve both genetic and environmental factors; however, these studies have not examined any maternal influence on children’s persistence development. The present study examined whether mothers’ persistence affects the development of persistence in children aged three to six years. In addition, the influence of mothers’ persistence and parenting style on children’s self-control and social development (prosocial behaviors and difficulties) were examined. Our results showed that maternal persistence is essential for the development of a child’s persistence. Children’s self-control and social development were also affected by the mothers’ persistence and parenting style. Our findings suggest that a child’s persistence develops under the influence of a familiar adult (i.e., mother) and characterizes their social development, highlighting the importance of persistence in parenting.